Minimal residual disease in cancer of the oesophagus and gastro-oesophageal junction - MacGuill, Martin James (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2009)
Epithelial tumours are the most common form of cancer and are responsible for the majority of cancer-related deaths in Western industrialized countries. Minimal residual disease following neo-adjuvant therapy or primary surgical therapy for epithelial tumours is believed to underlie therapy failure. We chose to study Oesophageal cancer in particular because it presents unique challenges. Despite Improvements in surgical therapies and the advent of multimodality regimens, the overall outlook remains generally bleak, and only 8-20% of patients are alive at 5 years.
Keywords: Clinical Medicine, M.D.; M.D. Trinity College Dublin